PERENCANAAN SISTEM DRAINASE KALI TENGGANG SEMARANG - Martin Martunas Agung P.S.; Riekea Astika Putri Gultom; Suripin Suripin; Dwi Kurniani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Kali Tenggang is one of the urban drainage systems in East Semarang. Kali Tenggang flows through industrial zones in Semarang, such as Kaligawe that has an important roles for regional economoy. Kali Tenggang which through downtown makes watershed of Kali Tenggang cannot out from flood disaster. There are many factors cause this disaster, like reducing channel capacity because of sedimentation, number of land subsidence, backwater and overflow from rivers around Kali Tenggang. Some of the attempt to solve this problem are redesign channel and build retention pond, so the live of the people who live around Kali tenggang can run well and prosper. Design of Retention Pond and redesign channel use HEC-RAS program with HEC-HMS’s discharge and cross section data as input data. Redesign channel planned on 9 sections,they are Majapahit,, Bugen, Tlogosari, Rel area, Muktiharjo, Dempellor, Terboyo, Pacar, and Tambakrejo. Construction of retention pond and redesign channel project spend Rp 122.269.035.885,00 and this project finished on 156 days.